Cash flow system development framework within integrated project delivery (IPD) using BIM tools. Issue 6 (3rd June 2021) - Elghaish, Faris; Abrishami, Sepehr; Abu Samra, Soliman; Gaterell, Mark; Hosseini, M. Reza; Wise, Richard
Abstract: Integrated Project Delivery (IPD) endeavour to revamp AEC project outcomes through a collaborative method of regulating project stakeholders' goals through creation of a platform that provide early participants involvement and shared risk and rewards. IPD does not include a tender stage to select the optimal bid, therefore, this article presents a methodology framework to develop a cash flow approach using BIM tools. This article adopts Activity Based Costing (ABC), due to its ability to allocate different costs precisely to each construction process. Given that the BIM and IPD target is to achieve the best collaboration among project parties, the proposed framework backing this by displaying all estimated cost data of each package as minimum/maximum estimated cash inflow, during the buyout stage, for informed decision making. This article extends the knowledge relating to IPD implementing process, as well as, improving cost management process based on BIM. Extant literature review highlights the gap of utilising BIM tools to develop cash flow curves, as well as the IPD cost structure requirements. To demonstrate the applicability and validity of the proposed model, it is applied to a real-life case study, which displays promising results in terms of developing IPD's cash flow management approach.